Strength of single- and double-gated injection moulded short glass fibre reinforced polycarbonate. (April 2013) - Hashemi, S
The effect of temperature, strain rate, moulding thickness and the mode of loading on weldline integrity of injection moulded polycarbonate (PC) reinforced with 10% and 30% by weight short glass fibres was studied. Results showed that tensile and flexural strengths of single-gated mouldings, σcs, increased with increasing fibre concentration, φf, in a linear manner, thus obeying the rule of mixtures for short fibre composites. The presence of weldlines in double-gated mouldings reduced tensile and flexural strength by as much as 70%. It was found that tensile and flexural strengths of double-gated mouldings, σcd, increased initially and reached a maximum before decreasing with increasing φf . However, for both single- and double-gated mouldings, the flexural strength values were consistently higher than tensile strength values. It was found that tensile strength of both single- and double-gated mouldings increased linearly with increasing ln(strain rate) and decreased linearly with increasing temperature. Tensile strength of single- and double-gated mouldings showed no significant variation with respect to the thickness of the moulding. The weldline integrity factor decreased with increasing fibre concentration and showed little variation with respect to temperature, strain rate and the thickness of the moulding.